Evaluation of the effect of allograft with doxycycline versus the allograft alone in the treatment of infrabony defects: A controlled clinical and radiographical study - Kulmeet Kaur; Poonam Sikri (Wolters Kluwer Medknow Publications, 2013)
Background: Successful prevention and treatment of periodontal disease are contingent on effective control of periodontopathic microbiota based on the premise of periodontal disease being infectious disorders. An anti-microbial agent, i.e., doxycycline has been incorporated into the allograft to control infection and facilitate healing during and after periodontal therapy. Materials and Methods: Using a split-mouth design, 15 patients showing clinical evidence of almost identical bilateral infrabony defects requiring bone grafting procedures were randomly selected. In each patient, infrabony defects on one side were designated as Group A (control group) and infrabony defects of the contralateral side of the same arch were designated as Group B (test group). Clinical assessment of probing pocket depth and attachment level and radiographic evaluation of the defect depth was done pre-operatively and at 12-week and 24-week post-operatively. The relative efficacy of the two treatment modalities was evaluated using paired Student's t-test and the comparative evaluation between the two groups over the 3 time intervals was done using independent Student's t-test. Results: Both the groups exhibited a highly significant reduction in probing depth and gain in clinical attachment level (CAL) and a linear bone fill at the end of 12 and 24 weeks. Comparative evaluation showed a statistically significant gain in bone fill in Group B as compared to Group A, whereas a non-significant reduction in probing depth and gain in CALs between the two groups at the end of 24 weeks (whereas mean reduction in probing depth and gain in CAL were also greater in Group B but the difference was statistically non-significant). Conclusion: The increase in linear bone fill in Group B signifies the role of doxycycline in augmenting regenerative potential of allograft by combating residual infection and through host modulation.